Razvoj majev in mlajev na Slovenskem - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 2008)
The treatise addresses the following questions: what are may branches, maypoles and St George festivals; when did they first appear; to which population group belonged these cultural elements; what were their meanings and how did they develop.
Keywords: ethnology; etnologija; floklore; mazpoles; Slovenci; Slovenes; Green George; letne šege; jurjevo; mythological school; jurjevanje; maji; Mayan Civilization; mlaji; zgodovinski pregled; kurenti